Walter Brueggemann permetafora-modellje, néhány kritika fényében - MÁTHÉ-FARKAS, Zoltán (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
Walter Brueggemann’s Trial Metaphor Model – In the Light of Some Critiques. Walter Brueggemann’s Theology of the Old Testament evoked a lot of criticism. His trial metaphor as a methodological frame is generally welcomed. But we recognize that the courtroom situation presented in Brueggemann’s way can be seen as a hermeneutical model for referentiality, that is to say: when we do not have any empirically verifiable evidence about God, the only chance for us is to accept the testimony of the biblical text. The rhetoric of the accepted testimony will constitute the reality after this. This opinion of Brueggemann is sharply criticized by many scholars. The present essay tries to answer ‒ in a modest way ‒ some of these judgments and concludes that the reality generated by the testimony can be known and understood better if its rhetoric is primarily analysed through literary study.